Heterogeneity of circulating tumor cells (CTCs) in patients with recurrent small cell lung cancer (SCLC) treated with pazopanib. (February 2017) - Messaritakis, I.; Politaki, E.; Plataki, M.; Karavassilis, V.; Kentepozidis, N.; Koinis, F.; Samantas, E.; Georgoulias, V.; Kotsakis, A.
Highlights: Pazopanib is a small molecule with a tyrosine multikinase inhibitor activity. CTCs detection could serve as a prognostic and predictive tool in SCLC. Pazopanib effect on CTCs was an early event, and even after one treatment cycle. Abstract: Objectives: To investigate the effect of pazopanib on different CTCs subpopulations in patients with recurrent SCLC and evaluate their clinical relevance. Methods: Peripheral blood was obtained before the administration of pazopanib (n = 56 patients), after the first cycle (n = 35 patients) and at disease progression (n = 45 patients). CTCs were detected by CellSearch and double immunofluorescent staining using antibodies against the cytokeratins (CK), TTF-1, CD56 and VEGFR2. Results: Before treatment, CTCs could be detected in 50% of patients by CellSearch; phenotypic characterization of CTCs demonstrated that 50%, 46.6% and 27.6% of patients had CD45 − /TTF1 +, CD45 − /CD56 + and TTF-1 + /CD56 + CTCs, respectively. Additionally, 59% of CTCs were TTF-1 + /VEGFR2 + and 53% CK + /VEGFR2 + . One pazopanib cycle resulted to a significant decrease of the number of CTCs (CellSearch: p  = 0.043) and CK + /VEGFR2 + cells ( p  = 0.027). At the time of PD, both the total number of CTCs ( p  = 0.027) and the number of the different subpopulations were significantly increased compared to post-1st cycle values; this increased CTCs number was associated with a significant increase of TTF-1 + /VEGFR2 + ( p  = 0.028) and CK + /VEGFR2 + CTCs ( p  = 0.018). In multivariate analysis, only the number of CTCs as assessed by CellSearch after one treatment cycle was significantly associated with OS (HR: 0.21; p  = 0.005). Conclusions: Pazopanib has a significant effect on different subpopulations of CTCs in patients with relapsed SCLC; the detection of VEGFR2 + CTCs during treatment could be a surrogate marker associated with resistance to pazopanib.